Вплив бактеріофагальної двониткової РНК на макрофаги у контексті пандемії COVID-19 - (:unkn) unknown (My University, 2025)
Метою роботи було дослідити вплив бактеріофагальної дволанцюгової РНК (Larifan) на метаболічний профіль ізольованих альвеолярних макрофагів (АМ) здорових мишей C57BL/6 та Balb/c різної статі та віку і моноцитів здорових чоловіків і жінок різного віку. Оцінку метаболічного профілю фагоцитів проводили за їх фагоцитарною активністю, оксидативним метаболізмом та експресією фенотипових маркерів поляризованої активації CD80 та CD206, які визначали методом проточної цитометрії. Показано, що Larifan стримує гіперзапальні реакції АМ, зберігаючи їх функціональні ознаки, типові для тканинних резидентних клітин. Більш виразна поляризація AM спостерігалася у мишей C57BL/6 з Th1-профілем імунної реактивності. АМ самиць обох ліній більш інертні до впливу препарату, а АМ старих самців обох ліній - найбільш чутливі. Реакція моноцитів більш виразна у мишей BALB/c з Th2-профілем імунної реактивності. Обробка препаратом пригнічує синтез АФК моноцитами незалежно від генотипу тварин, що свідчить про його протизапальні властивості. У мишей BALB/c спостерігали також посилення фагоцитарної активності та зниження антигенпрезентувальної здатності за рахунок зниження рівня експресії CD80. Larifan чинить протизапальну дію на моноцити чоловіків молодого та старшого віку, не впливає на клітини молодих жінок і справляє незначну прозапальну дію на моноцити літніх жінок. Це додатково підтверджує терапевтичний потенціал Larifan, враховуючи підвищену частоту вірусних інфекцій і більш серйозні запальні реакції у чоловіків порівняно з жінками, а також у літніх людей порівняно з молодими. Отримані результати вимагають подальших досліджень препарату, спрямованих на розробку індивідуальних планів його терапевтичного застосування залежно від віку та статі людини.

The study aimed to investigate the effect of bacteriophage-derived double-stranded RNA (Larifan) on the metabolic profile of isolated alveolar macrophages (AM) from healthy C57BL/6 and Balb/c mice of different sexes and ages, peripheral blood monocytes from healthy C57BL/6 and Balb/c mice, and monocytes from healthy male and female donors of different ages. The phagocyte metabolic profile was characterized by their phagocytic activity, oxidative metabolism, and the expression of phenotypic markers of polarized activation, including CD80 and CD206, which were examined by flow cytometry. Larifan restrains the hyper-inflammatory responses of alveolar macrophages (AM) while preserving their functional signatures, which are typical of patrolling tissue-resident sentinels. The more polarized AM activation was observed in C57BL/6 mice, characterized by Th1-shifted immune responses. AM from female animals of both strains were more resistant to the Larifan, and AM from old male animals from both strains were most susceptible. The monocyte response to the Larifan was more pronounced in BALB/c mice with Th2-shifted immune reactivity. Larifan inhibits ROS synthesis regardless of genotype, indicating its anti-inflammatory properties. In BALB/c mice, enhancement of phagocytic activity and a reduction in antigen-presenting capacity, demonstrated by a decrease in CD80 expression levels, were also observed. Larifan's modulatory effects are more pronounced in monocytes from healthy aged individuals. It exhibited an anti-inflammatory effect on monocytes taken from men of both age groups, while not affecting the cells of young women and exerting a slight proinflammatory effect on the monocytes of aged female donors. This further supports the therapeutic potential of Larifan, considering the increased incidence of viral infections and more severe inflammatory reactions in males compared to females, as well as in older persons compared to the young. Taken together, these results warrant further studies of Larifan, focusing on developing personalized treatment plans tailored to an individual's age and sex.
Impact of bacteriophage-derived dsRNA on macrophages in context of COVID-19 pandemic